Trends and impact of early intervention for communication disorders at AIISH - G, Malar; N, Sreedevi; C B, Suresh (Journal of All India Institute of Speech and Hearing, 2013)
Presence of disabilities like hearing impairment, mental retardation, cerebral palsy, autism spectrum disorders, etc. are found to inhibit the personal, social and productive life of any individual (INDG, 2011; Mauro, 2010; NICHCY, 2010). However, contemporary evidences in the field of rehabilitation for communication disorders suggest that early identification followed by prompt intervention to produce effective results in later educational and social life of the individual (Berrueta-Clement et al., 1984, qtd. in OERI, 2011; Hall, Oyer & Haas, 2001; Moeller, 1991). As a pioneering institute not only in India, but in the south-Asian region for rehabilitation for communication disorders; All India Institute of Speech & Hearing (AIISH) has been a trend setter in early intervention for children with communication disorders for nearly five decades. The current study was undertaken to examine the trends in early intervention at AIISH and its impact on beneficiaries. Two-hundred and five former early intervened clients of AIISH since 2003 were reached out through a survey type of research. Antecedent details of the nature of early intervention services availed, consequent progress in early communication skills, as well as current school performances of the participants were compiled. Analysis of the information using simple descriptive and correlation statistical measures revealed a satisfactory trend in early identification and timely intervention ensued by commendable influence on development of communication and academic skills, as well as social integration in the educational mainstream. The findings reaffirm convictions about need for early identification and comprehensive intervention for successful rehabilitation of young children with communication disorders (Hammes et al., 2002; Yoshinaga-Itano et al., 1998; Robinshaw, 1995; Ramkalawan & Davis, 1992; Markides, 1986).